Virological and immunological features of SARS‐COV‐2 infected children with distinct symptomatology. Issue 8 (16th July 2021) - Cotugno, Nicola; Ruggiero, Alessandra; Pascucci, Giuseppe Rubens; Bonfante, Francesco; Petrara, Maria Raffaella; Pighi, Chiara; Cifaldi, Loredana; Zangari, Paola; Bernardi, Stefania; Cursi, Laura; Santilli, Veronica; Manno, Emma Concetta; et al.
Abstract: Background: Although SARS‐CoV‐2 immunizations have started in most countries, children are not currently included in the vaccination programs; thus, it remains crucial to define their anti‐SARS‐CoV‐2 immune response in order to minimize the risk for other epidemic waves. This study sought to provide a description of the virology ad anti‐SARS‐CoV‐2 immunity in children with distinct symptomatology. Methods: Between March and July 2020, we recruited 15 SARS‐CoV‐2 asymptomatic (AS) and 51 symptomatic (SY) children, stratified according to WHO clinical classification. We measured SARS‐CoV‐2 viral load using ddPCR and qPCR in longitudinally collected nasopharyngeal swab samples. To define anti‐SARS‐CoV‐2 antibodies, we measured neutralization activity and total IgG load (DiaSorin). We also evaluated antigen‐specific B and CD8+T cells, using a labeled S1+S2 protein and ICAM expression, respectively. Plasma protein profiling was performed with Olink. Results: Virological profiling showed that AS patients had lower viral load at diagnosis ( p = .004) and faster virus clearance ( p = .0002) compared with SY patients. Anti‐SARS‐CoV‐2 humoral and cellular response did not appear to be associated with the presence of symptoms. AS and SY patients showed similar titers of SARS‐CoV‐2 IgG, levels of neutralizing activity, and frequency of Ag‐specific B and CD8+ T cells, whereas pro‐inflammatory plasma protein profile was found to be associated with symptomatology. Conclusion: We demonstrated the development of anti‐SARS‐CoV‐2 humoral and cellular response with any regard to symptomatology, suggesting the ability of both SY and AS patients to contribute toward herd immunity. The virological profiling of AS patients suggested that they have lower virus load associated with faster virus clearance. Abstract :